2010
DOI: 10.1111/j.1365-2354.2009.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological and immunohistochemical HER-2/neu statuses do not correlate and lack prognostic value for ovarian cancer patients

Abstract: The serodiagnostics of extracellular domain (ECD) HER-2/neu has turned into an evidenced-based tumour marker for HER-2/neu-positive breast cancer patients. This study investigated the clinical relevance of immunohistochemical and serum HER-2/neu in 44 patients with advanced ovarian cancer. The Hercept-Test® from DAKO Diagnostics was used to analyse immunohistochemical HER-2/neu expression. The HER-2/neu ECD in serum was determined quantitatively by Bayer Immuno 1™ Immunoanalyser. The HER-2/neu serum values wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…In a multi‐center randomized phase III trial of platinum‐based combinatorial chemotherapy, ErbB2 amplification was only seen in small percentage of participants and was not associated with response (Farley et al, 2009). Additionally, several studies have shown that ErbB2 status is not associated with any clinicopathological parameter such as progression free survival, stable disease, or overall survival in EOC (de Graeff et al, 2008; Hoopmann et al, 2010). These studies suggest that ErbB2's role in EOC may not be as important as our model interpreted it to be.…”
Section: Resultsmentioning
confidence: 99%
“…In a multi‐center randomized phase III trial of platinum‐based combinatorial chemotherapy, ErbB2 amplification was only seen in small percentage of participants and was not associated with response (Farley et al, 2009). Additionally, several studies have shown that ErbB2 status is not associated with any clinicopathological parameter such as progression free survival, stable disease, or overall survival in EOC (de Graeff et al, 2008; Hoopmann et al, 2010). These studies suggest that ErbB2's role in EOC may not be as important as our model interpreted it to be.…”
Section: Resultsmentioning
confidence: 99%
“…However, consistent with a mono-epitopic interaction with the antigen, we did not observe in vitro or in vivo degranulation in the presence of ECD HER2 . A serum concentration of ECD HER2 above 15 ng/ml is considered to be elevated in cancer patients, with highly elevated levels being above 100 ng/ml [58, 62]. The average concentration in the serum of patients with advanced disease is 35–40 ng/ ml [58, 59].…”
Section: Discussionmentioning
confidence: 99%
“…This detection rate is quite reasonable because HER-2/neu overexpression has been shown in primary ovarian tumor tissue in approximately 20% of cases. 33 It often has been asked whether surgery could contribute to the dissemination of tumor cells into the blood circulation. For ovarian cancer, the postoperative residual tumor is the most important prognostic factor.…”
Section: Characterization Of Ctcmentioning
confidence: 99%